REVITALISASI PENDIDIKAN PROFETIK ATAS KRISIS KEMANUSIAAN - Moh. Nor Afandi (Published by the Islamic Religious Education Study Program Faculty of Tarbiyah and Teacher Training Kiai Haji Achmad Siddiq University, Jember, East Java, Indonesia, 2022)
Pendidikan profetik dianggap berfungsi untuk mengatasi persoalan dan memberikan kontribusi atas segala ketimpangan yang terjadi terutama pada krisis kemanusiaan yang kini dihadapi oleh masyarakat modern. Persoalan fundamental adalah krisis moral dan krisis spiritual. Penelitian ini menggunakan Paradigma penelitian konstruktivis dengan pendekatan kualitatif deskriptif (Qualitative deskriptive) dengan jenis penelitian kepustakaan (Library Research). Pengumpulan data dilakukan dengan studi dokumenter. Analisis data menggunakan content analysis dan keabsahan data menggunakan Triangulasi Sumber. Penelitian ini menyimpulkan: 1) membangun pendidikan demokratis, menghilangkan dekotomi pendidikan, dan memaksimalkan peran profetik dalam pendidikan dengan menempatkan manusia sebagai subjek pendidikan; 2) liberasi terhadap sistem kehidupan yang terdapat dalam beberbagaiaspek, dan 3) menambah dimensi transendental dalam tranformasi dan komunikasi dengan Tuhan serta berlatih untuk mengembalikan kesadaran Ilahiah. Kata Kunci: Krisis Kemanusian; Pendidikan; Profetik; Revitalisasi Prophetic education functions to overcome problems and contribute to all inequalities that occur especially in the humanitarian crisis that is now faced by fundamental modern society, namely moral crisis and spiritual crisis. This study uses the constructivist research paradigm with a descriptive qualitative approach (Qualitative Descriptive) with the type of library research (Library Research). Data collection is done by documentary studies. Data analysis using content analysis and data validity using Source Triangulation. The results of this study are: 1) building humanist education, eliminating educational decotomy, and maximizing prophetic roles by placing humans as subjects of education; 2) liberation of education, reviving teaching and learning activities that are built on synergic cooperation between educators and students by being the subject of thinking and acting without any confinement of the surrounding environment and 3) adding to the transcendental dimension of transformation and communication with God and practicing to restore divine consciousness. Keywords: Humanitarian Crisis; Education; Prophetic; Revitalization